"Keep it Realistic": Reactions to and Recommendations for Physical Activity Promotion Messages From Focus Groups of Women. Issue 6 (July 2019) - Thai, Chan L.; Taber, Jennifer M.; Oh, April; Segar, Michelle; Blake, Kelly; Patrick, Heather
Purpose: Less than half of US adults meet the recommended guidelines of 150 minutes of exercise each week. Health promotion messages are frequently used to promote physical activity (PA); however, this messaging may be ineffective if it does not resonate with the target audience. The purpose of this exploratory study is to understand how women respond to examples of PA promotion messages. Approach/Design: A qualitative study. Setting: Washington DC Metro Area. Participants: Forty women, stratified by race/ethnicity (white, black, Latina) and level of self-reported PA (active, inactive). Method: Eight focus groups were conducted in which participants were shown 3 PA promotion messages representative of typical messaging strategies. Three researchers conducted a thematic analysis to code the data for emergent themes. Results: Current PA promotion messaging strategies do not resonate with women. Women want to see individuals with "realistic" bodies who look similar to them (eg, body shape, age, race/ethnicity), and for PA messaging to include daily activities as a way to be active. Conclusions: Public health practitioners who promote PA to women should consider developing messages that better resonate with women's dynamic roles and lifestyles. Successful strategies may include depicting busy lifestyles that PA may be physically and logistically difficult to fit into and using models with diverse body shapes.